Review of Ioannis K. Hassiotis, Ο Οδυσσέας στις θάλασσες του Νότου: Η ελληνική παρουσία στις υπερπόντιες κτήσεις της Ισπανίας (16ος–17ος αι.) [Odysseus in the southern seas: The Greek presence in the Spanish overseas territories (16th–17th century)] - Sakkas, Konstantinos (Historein, 2024)
Review of Ioannis K. Hassiotis, Ο Οδυσσέας στις θάλασσες του Νότου: Η ελληνική παρουσία στις υπερπόντιες κτήσεις της Ισπανίας (16ος–17ος αι.). [Odysseus in the southern seas: The Greek presence in the Spanish overseas territories (16th–17th century)]. Thessaloniki: University Studio Press, 2022. 448 pp.